Time overruns as opportunistic behavior in public procurement - Chiara D'Alpaos; Michele Moretto; Paola Valbonesi; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper considers the supplier's strategic delivery lead time in a public procurement setting as the result of the firm's opportunistic behaviour on the optimal investment timing. In the presence of uncertainty on construction costs, we model the supplier's option to defer the contract's execution as a Put Option. We include in the model both the discretion of the court of law in enforcing contractual clauses (i.e. a penalty for delays) and the quality of the judicial system. Then, we calibrate the model using parameters that mimic the Italian procurement for public works and calculate the maximum amount that a firm is willing to pay (per day) to postpone the delivery date and infringe the contract provisions. Our results show that the incentive to delay is greater the higher the construction costs and their volatility, and the weaker the penalty enforcement by the courts of law.
Keywords: D81; H54; H57; L51; 330; Strategic Time Overruns; Public Procurement; Real Options